2010
DOI: 10.1111/j.1468-1331.2010.03179.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of traumatic brain injury in an adult population - how to classify mild cases?

Abstract: The incidence rate falls within the wide range of previous published figures. Use of LOC or PTA as a criterion for mild TBI affects the incidence rate considerably as does the exclusion of mild cases treated out of hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 13 publications
2
22
2
1
Order By: Relevance
“…First, this study made use of a series of patients taken from clinical practice in a rehabilitation setting. While this does introduce some selectivity (e.g., the rate of mTBI at 55% of the patient sample is lower than in some population studies, such as Numminen, 2011), this allows for analysis of a broad range of injury severities and increases external validity. Second, patients with TBI were only included in this study if they were not engaged in compensation seeking and had passed validated measures of effort.…”
Section: Discussionmentioning
confidence: 96%
“…First, this study made use of a series of patients taken from clinical practice in a rehabilitation setting. While this does introduce some selectivity (e.g., the rate of mTBI at 55% of the patient sample is lower than in some population studies, such as Numminen, 2011), this allows for analysis of a broad range of injury severities and increases external validity. Second, patients with TBI were only included in this study if they were not engaged in compensation seeking and had passed validated measures of effort.…”
Section: Discussionmentioning
confidence: 96%
“…In the U.S., about 7,400 deaths, over 600,000 emergency department (ED) visits, and over 60,000 hospital admissions of children between 0 and 18 years of age were caused annually by head trauma [3,4]. Mild traumatic brain injury (MTBI), also known as cerebral concussion, is much more common than moderate or severe TBI [5,6]. Data from the U.S. Centers for Disease Control and Prevention (CDC) indicated that each year in the United States, as many as 75% of persons who had a TBI were MTBI [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are 1.7 million TBI cases diagnosed annually, 1 of which 70-80% are classified as mild. 2-6 TBI can result from motor vehicle accidents, falls, assault, strike or blows to the head, biking or sports accidents 7-16 as well as blast injuries from military conflict. 17-22 The direct and indirect cost of TBI is about $60 billion 1 annually, where 44% ($26.4 billion) 23 is associated with mild TBI.…”
mentioning
confidence: 99%